2017
DOI: 10.3748/wjg.v23.i18.3214
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease in liver transplanted patients

Abstract: Most common hepatobiliary manifestation of inflammatory bowel disease (IBD) are primary sclerosing cholangitis (PSC) and autoimmune hepatitis, ranking them as the main cause of liver transplantation (LT) in IBD setting. Course of pre-existing IBD after LT differs depending on many transplant related factors. Potential risk factors related to IBD deterioration after LT are tacrolimus-based immunosuppressive regimens, active IBD and cessation of 5-aminosalicylates at the time of LT. About 30% patients experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 94 publications
(175 reference statements)
0
3
0
Order By: Relevance
“…After LT, about 30% of patients report an improvement of IBD, while almost the same percentage of patients get worse. In addition, occurrence of de novo IBD can develop in approximately 14–30% of patients with primary sclerosing cholangitis (PSC) [ 61 ]. In this scenario, UC and CD may be refractory to standard treatment despite the use of post-LT immunosuppressive drugs and thus need the use of anti-TNF-α drugs.…”
Section: Liver-transplanted Patientsmentioning
confidence: 99%
“…After LT, about 30% of patients report an improvement of IBD, while almost the same percentage of patients get worse. In addition, occurrence of de novo IBD can develop in approximately 14–30% of patients with primary sclerosing cholangitis (PSC) [ 61 ]. In this scenario, UC and CD may be refractory to standard treatment despite the use of post-LT immunosuppressive drugs and thus need the use of anti-TNF-α drugs.…”
Section: Liver-transplanted Patientsmentioning
confidence: 99%
“…[ 5 , 11 ] Liver transplantation is the definitive treatment for patients with AIH and cirrhosis. [ 12 ] PSC and AIH are the main causes of liver transplantation in patients with IBD, and relapse of the disease occurs in 25% of cases. [ 12 , 13 ] Poor adherence to treatment and posttransplant follow-up were contraindications for performing the procedure in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Some immune-mediated conditions, such as autoimmune hepatitis and primary sclerosing cholangitis, have a strong association with IBD and are responsible for a large number of cases that require liver transplantations [ 2 ]. IBD prevalence and prognosis in liver transplant patients have been extensively studied over the years [ 3 , 4 ]. Verdonk et al has shown that 44% of liver transplant patients had active IBD post-transplant.…”
Section: Introductionmentioning
confidence: 99%